Effect of Age upon Lipofuscin Deposits in the Hepatic Cells of the Hawaii-Japanese and Costa Rican Males - Hananouchi, Motoo; Sato, Tsuneko; Tauchi, Hisashi (Nihon Rōnen Igakkai zasshi, 1980)
Quantitative analysis of the autofluorescent lipofuscin pigment granules in the human male autopsy cases of 153 Hawaii-Japanese (36-97 years of age) and 47 Costa Ricans (23-86 years of age) was made statistically. Amount of the pigment per hepatic cell and in a given area and also mean size of the pigment granules are larger in the central zone than in the peripheral zone in both Hawaii-Japanese and Costa Ricans. Number of hepatic cells with pigment granules in Hawaii-Japanese is larger in central than in peripheral zones, however, in Costa Ricans, there was no significant difference between them. There are no significant age differences in appearances of lipofuscin pigment in the hepatic cells in both cases of Hawaii-Japanese and Costa Ricans. The appearance of the pigment in case of Hawaii-Japanese is most remarkably rich compared among groups examined (native Japanese, U.S. Caucasians and Costa Ricans) even in younger age groups. There was no statistical significant correlation between the increase in amount of lipofuscin pigment and decrease in number of hepatic cells in both groups. The pigment accumulation in the hepatic cells seems to be influenced by a relationship betwen environmental especially nutritional and constitutional conditions of the individual, and is not necessarily considered to be an inherent part of the aging of the individual.